Hubungan Mutu Pelayanan Kesehatan Terhadap Kepuasan Peserta Bpjs Penerima Bantuan Iuran (PBI) Di Puskesmas Mamajang Kota Makassar - Aripa, Lusyana; Enol, Tarsisius Sandilius; Kartini, Kartini (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Patient satisfaction represents an emotional response that emerges after receiving health services, based on a comparison between patients’ initial expectations and the actual quality of care received. According to the World Health Organization (WHO), service quality is a critical component in achieving equitable health coverage. Globally, approximately 5.7 to 8.4 million deaths occur annually in low- and middle-income countries as a result of poor-quality health services. Objective: This study aimed to determine the relationship between health service quality and the satisfaction of BPJS Contribution Assistance Recipients (PBI) at the Mamajang Community Health Center, Makassar City. Methods: This research employed a quantitative approach with a cross-sectional study design. The study population consisted of BPJS PBI participants aged over 20 years who accessed services at the Mamajang Health Center between January and February 2025, totaling 318 individuals. The sample size was determined using the Slovin formula, resulting in 177 respondents. Data were analyzed using statistical tests to identify the relationship between various service quality dimensions and patient satisfaction. Results: The findings revealed that there was no significant relationship between service structure and patient satisfaction (p = 0.395). However, there was a significant relationship between service comfort (p = 0.000), information delivery (p = 0.000), and service timeliness (p = 0.000) with BPJS PBI participant satisfaction at the Mamajang Community Health Center. Conclusion: The study concludes that comfort, information delivery, and service timeliness are key determinants influencing patient satisfaction among BPJS PBI participants, whereas structural aspects of the health service show no significant association. Strengthening these dimensions of service quality is essential to improve overall patient satisfaction and optimize public health service delivery.